Approaches and Strategies in Reading Unfamiliar English Texts - Novalita Fransisca Tungka (Sintuwu Maroso Journal of English Teaching, 2019)
Reading is a skill mastered and gained through mindful effort. It is a complex skill, made up of different processes happening simultaneously through implementing various strategies used interchangeably. This article briefly discusses the approaches, models, and strategies in reading, especially reading unfamiliar texts.